وجهة نظر معلمي العلوم حول استخدام الطلبة للتكنولوجيا ومدى ارتباطه في تفكيرهم الابداعي - آية عبد المنعم محمد ميالي (My University, 2024)
Abstract The aim of the study was to identify Science Teachers’ Perspective Toward the Students Use of Technology and its Relationship to Their Creative Thinking. In addition to determine the differences in the level of creative thinking and using technology as perceived by teachers according to the variables of gender, qualification, experience years, and training courses number. To achieve that, the study was conducted on an available sample consisting of (95) science teachers in the Nablus directorate. The researcher used the descriptive approach in its co relational and analytical methods for its compatibility to the study targets. To gather data, the researcher prepared and designed tow tools, the first tool measures the creative thinking, and the second tool measures the using of technology. Principal component analysis and Cronbach’ alpha equation were conducted to ensure the validity and reliability of the study tools. To analyze data, SPSS software was used and the level of significance was set at (0.05). The results of the study showed that the levels of creative thinking and the using of technology from the perspective of science teachers in the Nablus directorate were high, as the means of response for the total score were (3.70, 3.69) respectively. Also, there was statistically significant impact of using technology on creative thinking as perceived by teachers (R²= 0.549; p = 0.01). furthermore, there were no statistically significant differences in the level of creative thinking and using technology as perceived by teachers according to the variables of gender, qualification, experience years. Whereas, statistically significant differences were found according to training courses number in favor of teachers having 10 training courses and above. The study recommends the necessity to hold permanently and regularly training courses for science teachers about the new teaching technology in science. Focusing on the development of creative thinking skills and self- learning for science students in the eight-grade. Keywords: Creative thinking, technology, public schools, science, Palestine.